Propuesta de un plan estratégico de marketing para la empresa de calzado Jessenia de la ciudad de Lago Agrio - Guacho Toabanda, Jessica Maribel (2016)
This research entitled "PROPOSAL FOR A STRATEGIC MARKETING PLAN FOR THE COMPANY OF FOOTWEAR JESSENIA CITY Lago Agrio" was conducted in compliance with regulations and standards established by the National University of Loja, to effect the efficient performance of the company investigated the overall objective was designed for the development of the research was to make a proposal for a strategic plan for the company's shoes Jessenia city Lago Agrio for which the respective processwas conducted with the requirements, with changes to the development of the company. The research was based using the methodology: the historical method used to learn the history of the company, deductive method to determine general conclusions based on the information obtained, inductive method which helped to obtain information about the market, statistical method I throw the numerical data of quantitative analysis: techniques that were used for data collection were techniques of direct observation interviews and surveys subsequently to all this the relevant literature review in which are the theoretical basis used for the preparation of this thesis adds . Data obtained in the implementation of 300 customer surveys and 4 employees which helped us to get accurate information on how to consider and wish the company, in what we refer interviews were applied to the manager- owner Sta. Jessica Guacho, which totally reliable and effective information was obtained. In the external analysis could build the matrix of external factors, in order to establish the opportunities and threats, assigning a weight to each which proceeded to obtain data is reflected those results are as follows: (2.70) is a value which reveals opportunities indicating their dominance. For the preparation of internal factors the information obtained from the survey and interviews applied was considered, which likewise assigned a weight according to their impact on the strengths and weaknesses so that we determine are the following results: (2.65) is the amount that indicates the strengths which we can define that the company does not have significant problems that prevent their permanence in the market. Finally, in the study conducted proceeded to the next development of the SWOT matrix to define the opportunities, threats, strengths and weaknesses which allows us to develop the matrix of high impact, by raising the following objectives: 1. To hold events to venture the quality and variety of footwear attracting potential customers, which requires an investment of $ 250.00; 2. Design and implement advertising plan through technological systems achieving the positioning of the company, which requires an investment of $ 1,470: 3. Increase promotions where customer loyalty is rewarded in turn have option to receive a free gift for bringing a new customer, which requires an investment of $ 1,265; 4. Develop a training plan for employees in order to improve its sales in the company's shoes Jessenia, $ 360.00, concluding with the 4 strategic objectives which gives a total of $ 3,345 to run the marketing plan for which each objective a goal to meet, tactics, strategy, activities, time and responsible for the target was raised, it tends to run serving the needs of the marketing company "FOOTWEAR JESSENIA", which aimed to enable the use and acceptance of resources for achieve the desired profitability in the company.